The Association between Parents´ Knowledge and Proper Use of Insulin in Patients with Type I Diabetes Mellitus - Jabbar, Ruqayah K; Yawuz Jamal, Mohammed (Journal of the Faculty of Medicine Baghdad, 2024)
Background: It is possible that treatment may not be successful, and the expenses of therapy may increase due to patients’ lack of knowledge and inappropriate conduct. Insufficient knowledge regarding the use of insulin can hinder its effectiveness and adherence. Therefore, it is crucial for diabetic patients to follow guidance on insulin management to ensure better outcomes.Objectives: to investigate the correlation between parents' knowledge of children with type I diabetes and their ability to properly administer insulin to their children in the outpatient diabetes clinic in Nasiriya City.Methodology: Aross-sectional study was conducted at the of Endocrinology and Diabetes in Nasiriyah, Iraq between October 4, 2022, and March 30, 2023. The study enrolled 180 children and adolescents diagnosed with type 1 diabetes mellitus. The surveys were translated into formal Arabic and administered through face-to-face interviews and patient-caregiver. The knowledge phase 15 questions, while the final segment on taking insulin had five questions. Blood samples were collected from the patients to measure their fasting blood sugar and Glycated hemoglobin. The collected data underwent descriptive analysis using SPSS version 25 software.Results: A total of 180 children and adolescents with type I diabetes were part of the study. The patient's average age was (10.75 ±4.36) years, and they had been diagnosed with type 1 diabetes for an average of (6.24 ±3.70) years. Their fasting blood sugar level was out of control (208.42 ±95.0 mg/dl) and their HbA1c level was (9.90±2.85%). Most of the patients (52.2%) were female and had only completed kindergarten (43.3%). The majority of caregivers were parents or guardians who were either illiterate (30.6%) or had an elementary education (33.9%).Conclusions:  The study concluded that most of the caregivers had poor behaviors and insufficient knowledge about insulin usage in type 1 diabetic patients.